Alleyway in which Artist Thuyên's home workshop is located - Lê Thái Hoàng Nguyên (22638911) (2025)
The entrance to Artist Thuyên's home workshop is flanked on the right by images of popular Vietnamese dishes and on the left by a partially-completed sign, both painted by the artist.